Persistent organic pollutant levels in human visceral and subcutaneous adipose tissue in obese individuals - Depot differences and dysmetabolism implications - Pestana, Diogo (2015)
Background: The role of persistent organic pollutants (POPs) with endocrine disrupting activity in the aetiology of obesity and other metabolic dysfunctions has been recently highlighted. Adipose tissue (AT) is a common site of POPs accumulation where they can induce adverse effects on human health. Objectives: To evaluate the presence of POPs in human visceral (vAT) and subcutaneous (scAT) adipose tissue in a sample of Portuguese obese patients that underwent bariatric surgery, and assess their putative association with metabolic disruption preoperatively, as well as with subsequent body mass index (BMI) reduction. Methods: AT samples (n=189) from obese patients (BMI ≥35) were collected and the levels of 13 POPs were determined by gas chromatography with electron-capture detection (GC-ECD). Anthropometric and biochemical data were collected at the time of surgery. BMI variation was evaluated after 12 months and adipocyte size was measured in AT samples. Results: Our data confirm that POPs are pervasive in this obese population (96.3% of detection on both tissues), their abundance increasing with age (RS=0.310, p<0.01) and duration of obesity (RS=0.170, p<0.05). We observed a difference in AT depot POPs storage capability, with higher levels of ΣPOPs in vAT (213.9±204.2 compared to 155.1±147.4 ng/g of fat, p<0.001), extremely relevant when evaluating their metabolic impact. Furthermore, there was a positive correlation between POP levels and the presence of metabolic syndrome components, namely dysglycaemia and hypertension, and more importantly with cardiovascular risk (RS=0.277, p<0.01), with relevance for vAT (RS=0.315, p<0.01). Finally, we observed an interesting relation of higher POP levels with lower weight loss in older patients. Conclusion: Our sample of obese subjects allowed us to highlight the importance of POPs stored in AT on the development of metabolic dysfunction in a context of obesity, shifting the focus to their metabolic effects and not only for their recognition as environmental obesogens.